A method to determine minimum design metal temperature of pressure vessels made from ferritic steel by Master Curve approach. (1st February 2020) - Zhou, Zhongqiang; Hui, H.; Zhang, Yalin; Cong, Xiangchun; Bai, Hui
Highlights: We found the distinguish the low temperature fracture toughness of steel well. Material with similar low temperature toughness can't be divided into the same impact exemption curve in ASME. Seven minimum design metal temperature (MDMT) curves are proposed based on different yield strengths and seven assumed reference temperature, T 0MC . The MDMT can be determined when the reference temperature and yield strength of steel are measured. SA508-3 and Q345R are used to illustrate the applicability of the MDMT curves for pressure vessels made from ferritic steel. Abstract: The four impact exemption curves in ASME are convenient to estimate the minimum design metal temperature (MDMT) of ferritic steel. However they can't distinguish low temperature fracture toughness of ferritic steel well. Materials with similar fracture toughness, divided into different impact exemption curves will have different MDMT and conservative degree. And the MDMT of ferritic steel are estimated by the steel grade. There are differences in toughness for steel with same steel grade from different factories and different heats and batches of the same factory. In this paper, the seven MDMT curves, identified with labels I, II, III, IV, V, VI and VII are proposed based on assumed yield strength and seven reference temperatures, ( T 0MC = 20 °C, 0 °C, −20 °C, −40 °C, −60 °C, −80 °C and −100 °C) which can cover the temperature range for commonly used pressure vessels made from ferritic steel. The MDMT for a ferritic steel can be determined once the reference temperature and yield strength are measured. SA508-3 and Q345R, as a representative of ferritic steel are used to illustrate the applicability of the MDMT curves.